Efforts to Increase Students Reading Interest on Educational Reference Through Classical Guidance and Counseling Experiential Learning Model - Tatik Sutarti (JETL (Journal of Education, Teaching and Learning), 2017)
The objective of the research is improving students’ reading interest on educational references through classical guidance and counseling experiential learning model. The research was carried out at STKIP Pacitan on the second semester in 2016/2017 academic year. The subject of the research was 20 fourth semester students of STKIP Pacitan. The method of the research was Classroom Action Research (CAR). The data was collected through 3 (three) stages namely: data reduction, data presentation, and data conclusion or verification. The research resulted that the use of classical guidance and counseling experiential learning model gave opportunity for students to deliver their ideas related with the problems in reading interest, and then, being solved together through critical thinking.